Teoria da Inteligência Monetária: Uma análise dos aspectos afetivos, comportamentais e cognitivos de gestores - Ferreira, Gabriel Borges (2019)
The Theory of Monetary Intelligence is a subject very little studied, until then only studies on the theory were realized in the United States, France, China, Macedonia and Czech Republic. This study investigated the level of Monetary Intelligence of public and private sector managers. For data collection, the Monetary Intelligence Scale was partially used. At the end, the answers of 193 participants were collected. Through the Model of Structural Equations, using the SmartPLS 3 Software, the relationship between the affective, behavioral and cognitive aspects of the monetary attitudes of these managers with their satisfaction with the income were calculated. After the hypothesis test, four of the eight initial propositions were confirmed. The affective, behavioral and cognitive aspects presented potential of formation and explanation on the Monetary Intelligence. The behavioral aspects were the only ones to present a positive relation with the satisfaction of the salary. Different from the results of Tang et al. (2015), the level of Monetary Intelligence of managers was not related to satisfaction with their income. It was also verified that the salary level does not exert the moderating effect on the relation between Monetary Intelligence and the satisfaction with the income of the managers. The results obtained in this work demonstrated the importance of research on this theory and the findings about behavior in relation to money. Also hold, indications for the development of future research on the Theory of Monetary Intelligence.